Postconditioning promotes recovery in the neurovascular unit after stroke - Esposito, Elga; Licastro, Ester; Cuomo, Ornella; Lo, Eng H.; Hayakawa, Kazuhide; Pignataro, Giuseppe (Frontiers in Cellular Neuroscience, 2023)
Background and purpose: Experimental studies suggest that ischemic postconditioning interferes with cell death mechanisms and reduces infarction during the acute phase after focal cerebral ischemia. Postconditioning may be a practically feasible way to promote stroke recovery, but many drawbacks prevent its clinical translation. First, all existing studies are mostly on acute 24 hr outcomes. Second, the mechanisms of protection and augmented long-term benefits remain unclear. Our study aims to define some of the mechanisms that explain long-term benefits of improved recovery. Methods: Male Sprague–Dawley rats were subjected to 100-minute transient middle cerebral artery occlusion (MCAO) or postconditioning (100-minute middle cerebral artery occlusion plus 10-minute reperfusion plus 10-minute reocclusion). After 3 days or 2 weeks, infarct volumes, western blot, and immunohistochemical markers of neurogenesis and angiogenesis were quantified. Fluorocitrate (FC) or saline were administrated ICV (intraventricular injection) every other day starting on day 5 after focal cerebral ischemia, animals were recovered for 2 weeks. Results: After postconditioning BDNF protein expression levels increased compared to animals subjected to MCAO. Immunostaining showed that BDNF increased specifically in astrocytes. Moreover, when astrocytes were metabolically inhibited by fluorocitrate the postconditioning neuroprotective effect together with the postconditioning-dependent new angiogenesis and neurogenesis , were no longer observed. Conclusions: These results suggest for the first time that therapeutic effects of postconditioning may involve the promotion of neurogenesis and angiogenic remodeling, via BDNF and MMP9 released by astrocytes, during the recovery phase after focal cerebral ischemia.